Dampak Pelanggaran Etika Bisnis terhadap Reputasi Perusahaan di PT Garuda Indonesia - Muhammad Fahmy Mayadi; Awang Rivaldo; Lukman Hakim; Mohamad Zein Saleh (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This paper analyzes the impact of business ethics violations on the reputation of PT Garuda Indonesia, Indonesia's national airline. This research examines various cases of business ethics violations that have occurred in the company, including corruption, misuse of funds, and flight safety violations. The analysis shows that business ethics violations have led to a decline in public trust, financial losses, and damage to the company's international image. This paper also discusses reputation recovery strategies that PT Garuda Indonesia can implement, such as good corporate governance, increased transparency and accountability, and effective public communication programs. This research highlights the importance of business ethics in building and maintaining corporate reputation, and provides recommendations for PT Garuda Indonesia to prevent future business ethics violations and rebuild public trust.